A Systematic Review: Prevention of Japanese encephalitis in Asia - Septiani, M; Prasetyo, S (KnE Life Sciences, 2019)
Japanese encephalitis ( JE) is one of the vector-borne diseases caused by infection with Japanese encephalitis virus, through the Culex tritaeniorrhynchus mosquito bites. Pigs and birds are the main reservoirs of JE viruses. JE is an important cause of encephalitis in most of Asia, with high case fatality rates and often significant neurologic sequelae among survivors. This study aimed to describe the prevention of JE in some countries in Asia. This study is a systematic review of 29 studies in Asia conducted in 2010 - 2017. It found that the most prevalent of JE prevention program in Asia is vaccination. It was recommended by the World Health Organization (WHO) to integrate JE vaccinations in national immunization programs and to prioritize in endemic areas. Some countries have well established or developing JE vaccination programs; those are Cambodia, China, India, Japan, Taiwan, Korea, Malaysia, Nepal, Sri Lanka, Thailand, and Vietnam. While some other countries in Asia have minimal or no JE vaccination programs, that are Bangladesh, Philippines, and Indonesia. JE prevention measures in some countries in Asia are the establishment of guidelines and service improvements, diseases and vectors/hosts surveillance, implementation of immunization programs, local vector control, education, and health promotion campaigns, and community engagement and environmental management that should focus on high-risk areas. The incidence of JE is decreased significantly in countries that have implemented JE vaccination programs. Keywords: Japanese encephalitis, prevention, Asia